Family Matters: Trauma and Quality of Life in Family Members of Individuals With Prader-Willi Syndrome - Bos-Roubos, Anja; Wingbermühle, Ellen; Biert, Anneloes; Graaff, Laura de; Egger, Jos (Frontiers in Psychiatry, 2022)
Background Prader-Willi syndrome (PWS) is a potentially life threatening, genetic developmental disorder that requires lifelong medical treatment and behavioral management. PWS has a major impact on the patient's social environment. In this study, we have explored traumatic life events and symptoms of posttraumatic stress disorder (PTSD) in family members of individuals with PWS. We have also assessed quality of life in relation to trauma manifestations. In addition, we have evaluated demographic characteristics such as living setting of PWS patients as well as PWS symptom severity. Methods Data of this observational study were obtained by means of the Life Events Checklist DMS-5, the Posttraumatic Stress Disorder Checklist DSM-5, the abbreviated World Health Organization Quality of Life questionnaire, the Lancashire Quality of Life Profile questionnaire, and a short demographic inventory. The study sample includes 98 adults aged 19 to 80 years (M = 49, SD = 15), who are relatives of 69 individuals with PWS aged 0 to 58 years (M = 19, SD = 13). Participants were recruited via the two Dutch patient associations PWS and the Dutch Digital Center of Expertise PWS. Results Life time prevalence of traumatic events (93%) was higher in family members of PWS patients (“PWS relatives”) than in the general Dutch population (81%). Of those who reported any traumatic event, almost half reported PWS-related events. The prevalence of probable PTSD was higher in PWS relatives (12.1%) than the general lifetime prevalence of PTSD (worldwide, and in the Netherlands 7.4%). Predominant trauma symptoms in PWS relatives were “negative changes in arousal and reactivity” and “negative changes in cognition and mood;” both significantly negatively related to quality of life. Symptom severity of PWS individuals, as well as the associated trauma symptom severity of their relatives increased with age of the PWS individual. The presence of trauma symptoms was less frequent among relatives of PWS individuals living in a care facility. Conclusions Having a relative with PWS is associated with higher prevalence of traumatic experiences and greater vulnerability to PTSD. Raising awareness in health care professionals of trauma symptoms in PWS relatives may contribute to effective treatment of their psychosocial stress. In addition, timely interventions might prevent family members from developing psychopathology like PTSD.